Intravenous administration of brain-targeted stable nucleic acid lipid particles alleviates Machado-Joseph disease neurological phenotype. (March 2016) - Conceição, Mariana; Mendonça, Liliana; Nóbrega, Clévio; Gomes, Célia; Costa, Pedro; Hirai, Hirokazu; Moreira, João Nuno; Lima, Maria C.; Manjunath, N.; Pereira de Almeida, Luís
Abstract: Others and we showed that RNA interference holds great promise for the treatment of dominantly inherited neurodegenerative disorders such as Machado-Joseph disease (MJD), for which there is no available treatment. However, successful experiments involved intracranial administration of viral vectors and there is a need for a safer and less invasive procedure. In this work, we successfully generated stable nucleic acid lipid particles (SNALPs), incorporating a short peptide derived from rabies virus glycoprotein (RVG-9r) and encapsulating small interfering RNAs (siRNAs), which can target mutant ataxin-3. The developed formulation exhibited important features that make it adequate for systemic administration: high encapsulation efficiency of siRNAs, ability to protect the encapsulated siRNAs, appropriate and homogeneous particle size distribution. Following optimization of the formulation and in vitro validation of its efficacy to silence the MJD-causing protein - mutant ataxin-3 - in neuronal cells, in vivo experiments showed that intravenous administration of RVG-9r-targeted SNALPs efficiently silenced mutant ataxin-3 reducing neuropathology and motor behavior deficits in two mouse models of MJD. To our knowledge, this is the first report showing beneficial impact of a non-viral gene silencing strategy in MJD and the first time that a non-invasive systemic administration proved to be beneficial on a polyglutamine disorder. Our study opens new avenues towards MJD therapy that can also be applied to other neurodegenerative diseases linked to the production of pathogenic proteins.